To find the inverse of the function \( y = 11^x \) in logarithmic form, we first rewrite the equation in the standard form.
Part a:
-
Start with the equation: \[ y = 11^x \]
-
To find the inverse, swap \( x \) and \( y \): \[ x = 11^y \]
-
Now, solve for \( y \) in terms of \( x \):
- Take the logarithm (base 11) of both sides: \[ \log_{11}(x) = y \]
Therefore, the inverse of \( y = 11^x \) in logarithmic form is: \[ y = \log_{11}(x) \]
Part b:
Graphical Representation:
-
Graph of \( y = 11^x \):
- This graph is an exponential curve that increases rapidly as \( x \) increases. It passes through the point \( (0, 1) \) since \( 11^0 = 1 \) and approaches the x-axis (but never touches it) as \( x \) approaches negative infinity.
-
Graph of \( y = \log_{11}(x) \):
- This graph is a logarithmic curve that increases slowly. It passes through the point \( (1, 0) \) since \( \log_{11}(1) = 0 \) and approaches the y-axis (but never touches it) as \( x \) approaches zero from the right.
Symmetry Discussion:
- The graphs of the functions \( y = 11^x \) and \( y = \log_{11}(x) \) are symmetric about the line \( y = x \).
- This symmetry arises because if you take any point \( (a, b) \) on the graph of \( y = 11^x \), you can find the point \( (b, a) \) on the graph of \( y = \log_{11}(x) \). Thus, they reflect across the line \( y = x \).
In summary:
- a. The inverse of \( y = 11^x \) in logarithmic form is \( y = \log_{11}(x) \).
- b. Both graphs exhibit symmetry about the line \( y = x \).